Occupational Health and Safety in the Food and Beverage Industry - Noroozi, Ebrahim; Taherian, Ali R. (CRC Press, 2023)
"The text highlights the importance of achieving a safe and healthy working environment in the food and beverage processing industry. It provides information on food and beverage manufacturing disease, injury management, safer steps for employees to get back to work, discusses food security, safety, biosecurity, defense food safety, and quality including food adulteration. Discusses fundamentals of occupational health and safety in the food and beverage industry. Highlight standards and legislations as related to occupational health and safety for food and beverage processing sectors. Covers hazards, elements, accident prevention, various hazards present in food and beverage sectors, and their disease and injury management. Explores ethical issues in agri-food processing sectors and their effects on sustainability. Introduces importance, organization, and management for food and beverage processing sectors to prevent losses. The text is primarily written for professionals in the fields of occupational health and safety, food engineering, chemical engineering, and process engineering"--